Systematic review and meta-analysis of the efficacy of benzodiazepines for dyspnea in patients with cancer. (12th January 2023) - Yasuda, Shuntaro; Sugano, Koji; Matsuda, Yoshinobu; Kako, Jun; Takagi, Yusuke; Watanabe, Hiroaki; Kasahara, Yoko; Goya, Sho; Kohara, Hiroyuki; Mori, Masanori; Nakayama, Takeo; Yamaguchi, Takashi
Abstract: Objective: the role of benzodiazepines in relieving dyspnea in patients with cancer has not yet been established. This systematic review and meta-analysis aimed to determine the efficacy and safety of benzodiazepines alone or in combination with opioids for dyspnea in patients with cancer. Methods: Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and Ichushi-Web were searched for articles published from database inception to 23 September 2019. Studies of benzodiazepines alone or in combination with opioids for dyspnea were included. The primary outcome measure was the relief of dyspnea. The secondary outcome measures were anxiety, somnolence and severe adverse events. Results: of 505 publications initially identified, two trials and one trial were included in the meta-analysis of midazolam alone and in combination with morphine, respectively. With regard to the relief of dyspnea, midazolam alone showed no significant difference compared with morphine alone, with a relative risk of 0.95 (95% confidence interval: 0.47–1.89). Meanwhile, midazolam plus morphine was significantly more effective than morphine alone, with a relative risk of 1.33 (95% confidence interval: 1.02–1.75). For anxiety relief, a meta-analysis could not be performed because of insufficient data. The incidence of somnolence and severe adverse events was not significantly different between the experimental and control groups for either midazolam alone or in combination with morphine. Conclusions: benzodiazepines alone do not significantly improve dyspnea compared with opioids alone, but a combination of benzodiazepines and opioids may be more effective. Evidence from randomized controlled trials focusing on patients with cancer has not been generated in recent years. Further appropriately designed randomized controlled trials are required. Abstract : The current systematic review did not demonstrate the efficacy of benzodiazepines alone for dyspnea in patients with cancer. However, an additive effect was suggested when used in combination with opioids.